Evolution of the Polish Innovation Policy - Dworak , Edyta (Comparative Economic Research. Central and Eastern Europe, 2010)
The knowledge and technology sector is underinvested in Poland, and, furthermore, its innovation position is far worse than in the majority of most European Union countries. The technological gap between Poland and European leading countries is quite significant. One has to adopt a proper innovativenss development strategy which would then constitute the basis for implementation of the adequate innovation policy. The innovation policy realized at present in Poland seems to be convergent with the assumptions of the EU- documents and OECD- reports. Nevertheless, numerous problems still require a solution. A key question that remains is the acknowledgement of a clear priority in the economic policy to R&D expenditure, financed both from the government’s budget and the private sector. It also seems necessary to adjust the tax system and the credit policy to the needs of the innovative economy. More importantly is developing a policy of an actual support of intellectual entrepreneurship that should aim towards creating advantageous development conditions for enterprises conducting research and producing high-tech products (particularly venture capital). These activities should also contribute to increase innovativeness of the Polish economy and affect the quality and rate of future economic growth.